On the military-political conditions of the 1918 turkish intervention on the Artsakh city of Shushi - Harutyunyan, Mher (History and Culture, 2025)
The policy of state terror and ethnic cleansing pursued by Turkey in Western Armenia, the pinnacle of which was the genocide of indigenous peoples - Armenians, Greeks and Assyrians, was exported to Eastern Transcaucasia in 1918, where a puppet Azerbaijan Republic was created with Turkish bayonets with a stolen name and unimaginable territorial claims. Only two years of the existence of democratic Azerbaijan are characterized by bloody strife, unpunished policies of state terrorism and ethnic cleansing. A significant part of the Armenian population of Eastern Transcaucasia became its victim, hundreds of thriving settlements were set on fire and destroyed, and the centuries-old cultural values ​​of the Armenian people were mercilessly destroyed, looted or appropriated.The Turkish occupiers, with the active participation of the Musavatists, first destroyed the villages of the Berdadzor subdistrict, cutting off the region from Zangezur, in order to suppress the resistance of the Armenians of Artsakh by force of arms. In 1918, the commander of the 2nd Turkish division stationed in Aghdam sent an ultimatum to the Artsakh government. Then on September 22, 1918, accompanied by local armed Tatars, the occupiers invaded sovereign Nagorno-Karabakh, destroying all border settlements with intense artillery fire. On September 25 of the same year, Turkish military units, accompanied by thousands of Tatars who wanted to destroy and plunder the occupied settlements, entered Shushi.